Permutation Tests for Stock Index Performance: Evidence from ESG Indices - Hübel, Benjamin; Scholz, Hendrik; Webersinke, Nicolas (2022)
The ongoing shift towards sustainable asset management fuels the demand for stock indices with improved ESG profiles. Such indices exhibit different performance metrics and risk characteristics compared to their conventional parent indices. At first sight, it might be tempting to assume that their improved ESG profiles cause the main differences. We introduce Monte Carlo permutation tests and apply them to two S&P 500 ESG indices and find, however, that claims about ESG ratings impacting index performance metrics are not supported by our results. We observe that the better ESG profiles of these indices go hand in hand with exposures to small or value companies, depending on the index construction. Thus, it is essential for investors to adequately assess the methodologies used in constructing ESG indices to make expedient investment and benchmark decisions.<br
Keywords: Permutations tests; ESG; stock indices; benchmarks